Camila the painting star - Salazar, Alicia, 1973- (Salazar, Alicia, 1973- Camila the star., 2025)
Camila is thrilled to be selling paintings of her abuella at a local bakery, but when a classmate tells her the paintings are ugly, Camila feels sad and considers quitting.